Reproductive and vegetative phenology of the micro endemic Stachytarpheta cassiae (Verbenaceae) - Guimarães, Gesline Ferreira (2023)
The flora of the Brazilian rupestrian grasslands represents a hotspot of species richness and endemisms. Stachytarpheta cassiae (Verbenaceae), is a micro endemic species, from which nothing is known. Here, we quantified the activity and intensity of vegetative and reproductive phenophases throughout 12 months and tested for their seasonality and their relationship with local climatic variables. Both vegetative and reproductive phenophases were continuous. No seasonality was observed in the vegetative phenophases and none of them was influenced by climatic variables. Only flower buds and mature fruits’ intensities showed seasonality in February (rainy season) and July (dry season), respectively. Accordingly, increased temperature and humidity combined explained increased production of flower buds whereas decreased rainfall explained increased mature fruits. Higher intensity in flower buds may respond to similar climatic conditions as other species in the community. However, S. cassiae is much different as it continues producing flowers continuously. Higher intensity of mature fruits in the dry season is expected as their seeds are abiotically dispersed. Due to constant flower and leaf production, S. cassia may be a key species for the conservation of many vertebrate and invertebrate species and for maintaining the biogeochemical functioning of the impoverished soils of the rupestrian grasslands.